Insights into action : successful school leaders share what works - Sterrett, William (ASCD, 2011)
This book focuses on relevant topics that face todays educational leaders, particularly those at the school level: teacher leaders, grade or department chairs, assistant principals, and principals. Each chapter weaves a narrative of a successful leader who embodies the characteristics that current research and theory have established as essential for success, examining a different topic while offering practical applications and ways to overcome barriers to success.